Islamic Strategy Offers in The Implementation of The Science of Mawarist in Society : Study Centre of Mawarits Studies UNIDA Gontor - Ria Rahma; Mohamed Shafei Moftah Bosheya (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2020)
According to Islam, this research aims to find out new offerings and strategies in implementing the science of mawarist in society, which were studied by CMS (Center for Mawarits Studies) UNIDA Gontor. Mawarits Science is one of the branches of science that must be studied by Muslims following with the advice of the Prophet Muhammad SAW because the mawarits science will be lost if no one learns and teaches it. Disputes between heirs often occur if the distribution of inheritance is considered unfair or not following by applicable law or norms. Inheritance matters are included in the civil realm, so laws are governing this issue. Sometimes in the distribution of inheritance using civil law, customary law, and Islamic inheritance law (mawarits). The CMS's primary task (Center For Mawarits Studies) is to educate Muslim families related to the science of mawarits. This research uses a sociological-normative approach with descriptive analysis to collect techniques with observation, interviews, and documentation. This study's results are several offers and education from CMS to the whole community, especially Muslim families, to implement the science of mawarits, including; forming KSM (Family Awareness of Mawarits) through studies in the mosque, seminars with the theme PSP method (Determination Before Distribution). Even though the distribution of assets uses the science of mawarist, the family still has to register the distribution of inheritance in the form of land and property to the local officials to bind legally. By understanding and implementing the science of mawarist, the whole community, especially Muslim families, have practiced sharia and aqeeda, hablun minallah, and hablun minannas.Tujuan dari penelitian ini adalah untuk mengetahui tawaran dan strategi baru menurut Islam dalam mengimplementasikan ilmu mawarist di masyarakat yang dikaji oleh CMS (Centre For Mawarits Studies) UNIDA Gontor. Ilmu Mawarits adalah salah satu cabang ilmu yang wajib dipelajari oleh umat Islam sesuai dengan anjuran Nabi Muhammad SAW karena ilmu mawarits ini akan hilang apabila tidak ada yang mempelajari dan mengajarkannya. Perselisihan ahli waris sering terjadi apabila dalam pembagian harta warisan dirasa tidak adil atau tidak sesuai dengan hukum atau norma yang berlaku. Masalah waris adalah termasuk dalam ranah perdata sehingga ada undang-undang yang mengatur masalah ini. Adakalanya dalam pembagian warisan menggunakan hukum perdata, hukum adat dan hukum waris Islam (mawarits). Tugas utama CMS (Centre For Mawarits Studies) adalah mengedukasi keluarga muslim terkait ilmu mawarits.Penelitian ini adalah penelitian kualitatif yang menggunakan pendekatan sosiologis-normatif dengan analisis deskriptif, adapun teknik pengambilan data dengan observasi, wawancara dan dokumentasi. Hasil dari penelitian ini adalah ada beberapa tawaran dan edukasi dari CMS untuk keluarga muslim untuk mengimplementasikan ilmu mawarits, diantaranya adalah; membentuk KSM (Keluarga Sadar Mawarits) melalui kajian- kajian di Masjid, Seminar mawarist dengan tema PSP (Penentuan Sebelum Pembagian), dan Tallaqi Kitab Mawarits. Meskipun dalam pembagian harta menggunakan ilmu mawarist akan tetapi keluarga tersebut tetap harus mendaftarkan warisan berupa tanah atau property ke pejabat setempat sehingga berkekuatan hukum tetap. Dengan memahami dan mengimplementasikan ilmu mawarist seluruh masyarakat khususnya keluarga muslim telah menjalankan ilmu syariah dan aqidah, hablun minallah dan hablun minannas